FEATURES OF INCLUSIVE PHYSICAL EDUCATION OF PRESCHOOL CHILDREN WITH GENERAL UNDEVELOPMENT OF SPEECH - Bushmanova, T.S.; Fendel, T.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and experimentally prove the effectiveness of the methodology of inclusive physical education of preschool children with general underdevelopment of speech by means of fitness. Methods and structure of the study. The pedagogical experiment was carried out on the basis of preschool educational institutions in the city of Tchaikovsky. The study involved preschool children of five-six years old with general underdevelopment of speech and their peers with normative speech development attending groups of a combined type. In order to determine the effectiveness of the methodology in preschoolers, changes in indicators of physical development and physical fitness, the level of speech development and communication skills were assessed. Results and conclusions. The methodology of inclusive physical education of preschoolers with general underdevelopment of speech is based on the complex use of fitness means (classical aerobics, step, fitball and logo aerobics, stretching and yoga), outdoor games, finger gymnastics, breathing exercises and exercises with speech material. Based on the results of the study, the following conclusions were made: the experimental methodology, created taking into account the peculiarities of the psychomotor development of children with general underdevelopment of speech, allows for a comprehensive solution of the problems of inclusive physical education; the implementation of the methodology contributes to the growth of physical fitness and the level of communication skills of preschoolers who participated in the experiment. There is a statistically significant positive dynamics of speech development indicators in children with general speech underdevelopment.